The Penta Helix Collaboration Model for the Implementation of the Touris Alley Program in Makassar City - Haerul, Haerul; Anshari, Anshari; Andi Cudai Nur (Tinta Emas Publisher, 2024)
This study aims to describe and analyze the Penta Helix collaboration model for the implementation of the Lorong wisata program in Makassar City. The research used a qualitative descriptive method with a phenomenological approach. Data were collected through interviews, observations, and documentation, with primary data sources from informants, such as heads of agencies, sub-district heads, village heads, communities/visitors, micro, small and medium enterprises academics, communities, and media, as well as secondary data from related documents. The main research instrument is the researcher himself, supported by tools such as voice recorders and cameras. Data analysis techniques include collection, condensation, data presentation, and conclusion drawing and verification. Data validation was done by triangulation to ensure the validity and accuracy of the findings. The results showed that the Penta helix collaboration model of implementing the Lorong wisata program in Makassar City involved the government, private sector, academics, community, and media. The government plays an important role in making policies, regulations, and providing infrastructure, while the private sector supports through partnerships, social responsibility. Academics are involved in research and training, communities play an active role in cultural and environmental preservation, and local initiatives. Media plays a strategic role in program promotion and monitoring. This inter-actor collaboration has not been maximally implemented in various tourist alleys in the city of Makassar.